POTENTIAL OF HALAL TOURISM INDUSTRY IN INCREASING REGIONAL INCOME THROUGH REGIONAL TAX AND RETRIBUTION IN TOJO UNA-UNA REGENCY - Rustan, Fajar Eko Purnomo; Sahib, Muhammad Khaedar (Jurnal Ilmiah Al-Tsarwah, 2023)
This study aims to identify the potential of the halal tourism industry in the Tojo una una regency, Central Sulawesi Province, Indonesia. The method used is descriptive qualitative method with data collection techniques through surveys, documentation and observations. This study uses spatial analysis and snowball sampling to analyze and collect data on the distribution of accommodation, attractions and tourist attractions at the research location. The results showed that Tojo una-una district had a population of 165,574 people, with a density of 29 people/kmÂ² and about 91.22% (151,327 people) embraced Islam based on data from the Ministry of Religion in 2020. For the land area, it is estimated at around 5,721.51 Km2 or 8.41 percent of the land area of Central Sulawesi Province. The sea area reaches approximately 3,566.21 Km2. With a beach length of approximately 951.115 Km. Tojo Una-Una commonly abbreviated as Touna, which is a land area and a group of islands. This has become a huge potential in shaping the halal island tourism industry in the district. Tojo Una-una with good and professional handling and management, and of course it will become a source of local revenue through local taxes and retribution